The Lithospheric Structure of Antarctica from Geophysical–Petrological Modelling - Pappa, Folker (2019)
In this thesis, satellite gravity data are combined with seismic findings to invert for the Moho depth of Antarctica. The results suggest a significantly lower density contrast between crust and mantle underneath East Antarctica compared to West Antarctica. Accounting for that, combined geophysical-petrological modelling of the lithosphere in 2-D is conducted along a well studied profile to test different Moho depth scenarios. However, even though multiple geophysical observables are considered in an integrated manner, neither of the competing scenarios can be validated or refuted with this approach. This demonstrates the need for comprehensive modelling in 3-D. By utilizing satellite gravity gradient data in a thermodynamically self-consistent framework, this dissertation establishes a 3-D model of the Antarctic lithosphere and sublithospheric upper mantle. A new Moho depth map of the continent is derived that is in good agreement with independent seismic estimates. It also exhibits detailed variations for so far scarcely explored areas. Total lithospheric thickness values of the presented model confirm the marked contrast between West Antarctica (<100 km) and East Antarctica (up to 260 km). The inferred deep thermal field is used to estimate 3-D viscosities of the mantle for GIA modelling. Coupled with present-day uplift rates from GPS, the relatively low viscosity values suggest a bulk dry upper mantle rheology. Finally, the crustal part of the 3-D density model is tested against recent airborne gravimetric data. The short-wave-length residual signal is inverted for near-surface density variations within the crust with the aim to refine the continental lithospheric model on a regional scale. These two applications demonstrate the potential of the presented model for further regional and continental-scale studies of Antarctica. In dieser Dissertation werden Satellitenschweredaten zusammen mit seismischen Befunden dazu verwendet, Inversionsrechnungen zur antarktischen Mohotiefe durchzuführen. Die ...